Indole signalling and (micro)algal auxins decrease the virulence of Vibrio campbellii, a major pathogen of aquatic organisms. (3rd April 2017) - Yang, Qian; Pande, Gde Sasmita Julyantoro; Wang, Zheng; Lin, Baochuan; Rubin, Robert A.; Vora, Gary J.; Defoirdt, Tom
Summary: Vibrios belonging to the Harveyi clade are major pathogens of marine vertebrates and invertebrates, causing major losses in wild and cultured organisms. Despite their significant impact, the pathogenicity mechanisms of these bacteria are not yet completely understood. In this study, the impact of indole signalling on the virulence of Vibrio campbellii was investigated. Elevated indole levels significantly decreased motility, biofilm formation, exopolysaccharide production and virulence to crustacean hosts. Indole furthermore inhibited the three‐channel quorum sensing system of V. campbellii, a regulatory mechanism that is required for full virulence of the pathogen. Further, indole signalling was found to interact with the stress sigma factor RpoS. Together with the observations that energy‐consuming processes (motility and bioluminescence) are downregulated, and microarray‐based transcriptomics demonstrating that indole decreases the expression of genes involved in energy and amino acid metabolism, the data suggest that indole is a starvation signal in V. campbellii . Finally, it was found that the auxins indole‐3‐acetic acid and indole‐3‐acetamide, which were produced by various (micro)algae sharing the aquatic environment with V. campbellii, have a similar effect as observed for indole. Auxins might, therefore, have a significant impact on the interactions between vibrios, (micro)algae and higher organisms, with major ecological and practical implications.